Mobility in Dhakal’s Seti Pani Kali Pani - Kattel, Achut Raj (Mindscape: A Journal of English & Cultural Studies, 2023)
This research focuses in the area of niyatra, a Nepali term to denote a travel writing with the writer’s personal feelings and experiences. Prateek Dhakal’s Seti Pani Kali Pani picturizes many distant villages and hillsides of western Nepal and Nainital, India. This research is helpful to introduce the local area into the international arena and Nepali niyatra theory and literature in global context. It adopts Balkrishna Pokhrel, Nirmohi Byaas and Jaya Chhangchha’s theory on niyatra as research approach. The research also borrows concepts of travel writing proposed by some other western theorists like Carl Thomson and Mary Baine Campbell. For them, mobility is a key point of travel writing in general and niyatra literature in particular. This research addresses the issue how the theme of mobility is dominating in the text. The major objective of the research is to point out the movement from the beginning to the end of the text. The findings present many evidences of movement in Dhakal’s Seti Pani Kali Pani. To show the mobility, the description of landscape and places, society and culture and events and lifestyle in the text is analyzed. The research concludes that Dhakal’s Seti Pani kali Pani has the theme of mobility. This text has to be studied further by using another theme of Niyatra that is depiction of local.